Effect of Topical Versus Sub-conjunctival Anaesthesia during Administration of Intravitreal Bevacizumab Injection: Doi: 10.36351/pjo.v37i4.1249 - Rizwan, Amna; Zafar, Rabeeah; Asghar, Asfandyar; Obaid, Naila; Naeem, B A (Pakistan Journal of Ophthalmology, 2021)
Purpose: To compare the anesthetic effect of topical proparacaine hydrochloride 0.5% with sub-conjunctival lidocaine 2% for intravitreal injection of Bevacizumab. Study Design: Quasi experimental study. Place and Duration of Study: Department of Ophthalmology Fauji Foundation Hospital, Rawalpindi, from July 2017 to January 2018. Methods: Sixty 60 patients who needed intravitreal Bevacizumab were included in the study after approval from the ethical review board. Exclusion criteria were patients with conditions that could affect pain sensation, acute ocular inflammation, history of intravitreal injection, using systemic analgesic/sedatives, uncooperative patients and unable to understand the pain scale. Written informed consent was taken. Name, age, gender, diagnosis, previous intravitreal injection, hospital registration number, address and contact numbers were noted. Patients were briefed about the visual analogue scale. Patients were divided into two groups. Group A received proparacaine drops and group B was given subconjunctival lidocaine injections before intravitreal bevacizumab. Results: The mean age of patients in this study was 60.38 ± 10.55 years. There were 03 (5.0%) males and 57 (95.0%) females. Majority of the patients (30%) presented with choroidal neovascularization followed by diabetic maculopathy, vitreous hemorrhage, central retinal vein occlusion and proliferative diabetic retinopathy. Mean pain score among both the groups was 3.67 ± 1.97 (topical group) and 1.70 ± 1.51 (sub-conjunctival group) respectively which was statistically significant (p-value 0.000). Among age, diabetes, duration of diabetes and hypertension, only hypertension had moderate correlation with the pain score (correlation coefficient = 0.316, p values = 0.017). Conclusion: Sub-conjunctival anaesthesia results in less pain during intravitreal drug administration as compared to the topical anaesthesia. Key Words: Intravitreal injections, Bevacizumab, Intravitreal Anti-VEGF, Anesthesia.